Analisis Efisiensi Pemasaran Cabai Merah (Capsicum annum L.) di Kecamatan Watang Pulu Kabupaten Sidenreng Rappang - Rasidin Rasidin; Satri Fitra Tanro; Ismail Ismail; Rusnah Rusnah (Universitas Muhammadiyah Purworejo, 2021)
Fluctuations in production and prices are a problem faced by farmers in the red chili farming, so that it has an impact on the level of farm income obtained. This study aims to analyze the efficiency of marketing of red chili in Watangpulu District, Sidrap Regency. The number of samples or respondent farmers is determined by census, that is, the entire population in the research location is used as a sample or research respondent, while the red pepper respondent traders are determined using the snowball sampling method or following the marketing channel / chain formed based on instructions from the red chili farmers. The research data was taken in May-July 2018. Data analysis used was descriptive qualitative and quantitative. Marketing efficiency is analyzed using market structure, market behavior, and market performance. The results showed that the EP value was 4.87%, so the commodity farming business was very efficient to be undertaken.